Position & Responsibilities of Notaries in Implementing Circular Resolutions of Foreign-Owned Branch Companies - Yeni Amalia; Amin Purnawan; Djunaedi Djunaedi (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2021)
This study aims to determine the position and responsibilities of a notary in the organs of a Limited Liability Company. There are two types of Limited Liability Company, namely Public Company and Private Company. In a closed company, it is very possible to make circular decisions because the number of shareholders is not as many as a public company. The approach method used in this study is an empirical juridical approach, which is an approach that examines secondary data first and then proceeds with conducting primary data research in the field. Circular decisions are made when it is not possible for a Limited Liability Company to hold a General Meeting of Shareholders or an Extraordinary General Meeting of Shareholders whose provisions can be seen in Article 91 of the UUUP. In Indonesia and even around the world, we are facing a pandemic due to Corona Virus Disease or COVID-19. For a Limited Liability Company whose shareholders are foreigners, a Foreign Investment Limited Company (PMA), of course, cannot come to the position of a Limited Liability Company in Indonesia. So that it is done through video conference whose provisions can be found in Article 77 of the Company Law. Notaries are responsible for making Circular Deeds that do not violate the provisions of the Company Law. The position of the Notary appointed to make the deed of the Circular Decree of the Company can be selected from all over Indonesia. As long as the parties are facing the Notary. However, if a Notary is appointed to follow the process of implementing the Circular Decision, it must be a Notary who has the same position as the Limited Liability Company or may also have a different position but is still in the same province from the position of the Notary appointed to follow the Circular Decision of the Shareholders.